2018
DOI: 10.1371/journal.pone.0190347
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of relative systemic hypertension in adults with sickle cell disease in Ghana

Abstract: Individuals with sickle cell disease particularly with the homozygous (SS) genotype historically have relatively low blood pressure. Nonetheless, they develop vasculopathy-associated organ dysfunction and the risk of organ dysfunction increases at blood pressures that are normal in the general population. This phenomenon is termed relative systemic hypertension (RSH) with a systolic blood pressure range of 120-139 mmHg, and diastolic blood pressure range of 70-89 mmHg. The significance of RSH lies in its assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 20 publications
2
11
2
Order By: Relevance
“…In contrast to this study, studies by Benneh-Akwasi Kuma et al, [29], indicated the risk of relative systemic hypertension and hypertension in sickle cell subjects. Benneh-Akwasi Kuma et al [29] corroborate studies of sickle cell subjects with low blood pressure adding that relative systemic hypertension appeared in male subjects with a steady increase in age, whereas, hypertension is uncommon and appears in subjects having a medical history of hypertension.…”
Section: Discussioncontrasting
confidence: 96%
“…In contrast to this study, studies by Benneh-Akwasi Kuma et al, [29], indicated the risk of relative systemic hypertension and hypertension in sickle cell subjects. Benneh-Akwasi Kuma et al [29] corroborate studies of sickle cell subjects with low blood pressure adding that relative systemic hypertension appeared in male subjects with a steady increase in age, whereas, hypertension is uncommon and appears in subjects having a medical history of hypertension.…”
Section: Discussioncontrasting
confidence: 96%
“…Our prevalence is similar to that of 45% reported by Benneh-Akwasi Kuma et al in Ghana [20] as well as of 44% found by Makubi et al [21] and Gordeuk et al [6]. However, it is somewhat higher than that of 17% found by Becker et al [5] and Bodas et al [4], respectively.…”
Section: Discussionsupporting
confidence: 90%
“…25 It has also been shown that patients with SCD and relative hypertension (high-normal blood pressure values of systolic 120-139 mm Hg and diastolic blood pressure 70-89 mm Hg) have both higher seCr levels and an increased risk of pulmonary hypertension when compared with SCD patients with lower blood pressures. 26,27 Microalbuminuria (defined as .4.5 mg/mmol) is an early manifestation of SCN, reaching a prevalence of over 50% in older patients. 28 In 4% to 12% of the patients, the proteinuria may progress to end-stage renal disease needing renal replacement therapy that is associated with increased mortality.…”
Section: Comments On Patients 1 Andmentioning
confidence: 99%